Prosodic features of situational variation across nine speaking styles in french - Prsir, Tea; Goldman, Jean-Philippe; Auchlin, Antoine (Journal of Speech Sciences, 2021)
This paper presents results from an on-going study of prosodic and phonostylistic variation across speaking styles, i.e., acoustic images associated to types of language production, also called phonogenres. It extends previous work in (1, 2) by enlarging the corpus (C-PhonoGenre, 8 hours) and by exploring a more comprehensive collection of genres. The situational parameters in (3, 4) are reduced to four situational features, each admitting three values, the combination of which differentiates sub-phonogenres. The main goal of this study is to establish correlations between the situational and prosodic features of discourse. Corpus processing, annotation and measure calculation are performed semi-automatically, through a set of tools implemented under Praat and manual steps. Rhythmical measurements by DurationAnalyser (5) combined with the output of ProsoReport (6) produce an acoustic analysis of the differences between phonogenres. A large number of micro- and macro-prosodic measures provide a finegrained ‘prosometric’ description. This article presents the methodology for collecting the corpus, and results for the phonogenres.